Analysis of the Cash Disbursement Accounting System for Building Maintenance Processes at PT Bernofarm Pharmaceutical Company - Icha Dwi Sabrina; Sri Trisnaningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the cash disbursement accounting system for building maintenance at PT Bernofarm Pharmaceutical Company, a national pharmaceutical firm that has implemented an Enterprise Resource Planning (ERP) system. The primary issue addressed is the effectiveness of internal control mechanisms in handling cash disbursements, particularly cash transactions that are susceptible to errors and fraud. A qualitative descriptive case-study approach was adopted, using the COSO Framework—including control environment, risk assessment, control activities, information & communication, and monitoring. Data were collected through direct observation, interviews, and internal document analysis. Findings indicate that PT Bernofarm has implemented segregation of duties, tiered authorizations, and effective use of ERP for recording and disbursing funds. Nonetheless, weaknesses were found regarding the timely submission of cash transaction receipts and delays in physical document reporting, which affect data accuracy. Consequently, strengthened reporting procedures and a more comprehensive digital archiving system are recommended. This research offers practical contributions to reinforcing digital-based cash disbursement accounting systems and highlights the importance of adaptive internal control in the context of cash transactions.